Kinetic sorption of contaminants of emerging concern by a palygorskite-montmorillonite filter medium. (June 2017) - Berhane, Tedros M.; Levy, Jonathan; Krekeler, Mark P.S.; Danielson, Neil D.
Abstract: Kinetic sorption of bisphenol A (BPA), carbamazepine (CMZ) and ciprofloxacin (CIP) by three palygorskite-montmorillonite (Pal-Mt) granule sizes was studied. For BPA, CMZ and CIP, apparent sorption equilibrium was reached within about 3, 5 and 16 h, respectively. The highest and the lowest sorption capacities were by the small and the large granule sizes, respectively. Experimental results were compared to various sorption kinetics models to gain insights regarding the sorption processes and achieve a predictive capacity. The pseudo-second order (PSO) and the Elovich models performed the best while the pseudo-first order (PFO) model was only adequate for CMZ. The intraparticle-diffusion (IPD) model showed a two-step linear plot of BPA, CMZ and CIP sorption versus square root of time that was indicative of surface-sorption followed by IPD as a rate-limiting process before equilibrium was reached. Using the pseudo-first order (PFO) and the pseudo-second order (PSO) rate constants combined with previously-established Langmuir equilibrium sorption models, the kinetic sorption ( k a ) and desorption ( k d ) Langmuir kinetic rate constants were theoretically calculated for BPA and CIP. Kinetic sorption was then simulated using these theoretically calculated k a and k d values, and the simulations were compared to the observed behavior. The simulations fit the observed sorbed concentrations better during the early part of the experiments; the observed sorption during later times occurred more slowly than expected, supporting the hypothesis that IPD becomes a rate-limiting process during the course of the experiment. Highlights: BPA, CMZ & CIP reached equilibrium sorption onto palygorskite within 3, 5 and 16 h. Sorption capacities were inversely related to palygorskite granule size. Pseudo-second-order model fit all sorption data well. Langmuir kinetic rate constants were theoretically derived for predictive capacity. Model fits indicated fast surface sorption followed by intraparticle diffusion.